Choosing Technical Education and Vocational Training: A Narrative Inquiry - Maskey, Sanam (Journal of Education and Research, 2019)
Technical education and vocational training (TEVT) have been given a special place in the national development plan as well as in the educational policies of Nepal. The recent allocation of Rs. 1.38 billion by the government for the fiscal year 2019/20 for providing employment-related trainings and establishing technical schools in the country supports this claim. The government has recognized its potential in being able to alleviate poverty, improve livelihood strategies and provide employment opportunities. Adopting a narrative inquiry method, I interviewed three participants to explore the perception of youths towards this sector. The study revealed that one of the main barriers in choosing technical education and vocational training is the high value the society places upon general education in comparison to vocational education. It also revealed how we have been hegemonised by the ideologies flouted by the dominant class in society and readily give consent to these ideas. I argue that though the government has placed due emphasis on TEVT, its successful implementation can only be possible when the social perception on the divide between general education and technical and vocational education is brought to an end.